Clinical characteristics of patients with pulmonary sarcoidosis treated with systemic steroids in Japan - Sawahata, Michiru; Kimura, Hirokazu; Hattori, Takeshi; Tamada, Tsutomu; Bando, Masashi; Maemondo, Makoto; Kawanobe, Takeshi; Kono, Chiyoko; Yamaguchi, Tetsuo; Shijubo, Noriharu; Suda, Takafumi; Konno, Satoshi (Frontiers in Medicine, 2025)
BackgroundSevere pulmonary sarcoidosis is less common in Japan than in other countries, and the actual clinical situation of systemic steroid use in Japan requires clarification.MethodsThis study analyzed 65 patients with histologically diagnosed sarcoidosis who initially received systemic steroids for pulmonary lesions and made regular outpatient visits to Hokkaido University Hospital, JR Sapporo Hospital, or JR Tokyo General Hospital in September 2017.ResultsMedian age at diagnosis was 35 (interquartile range [IQR] 26–48) years. Thirty-four patients (52.3%) were men. Median time from diagnosis to steroid initiation was 5 (IQR, 1–9) years. Median maximum steroid dose was prednisolone (PSL) 30 (range 5–60) mg/day. Immunosuppressants were used in 19 patients (29.2%). Twenty-one patients (32.3%) received PSL ≤ 10 mg/day and 7 (10.8%) received 5 mg/day. The PSL ≤ 10 mg/day group included a significantly lower proportion of men than the group treated with higher doses (33.3% vs. 61.4%, p = 0.034). Most cases were effectively treated, but some required long-term steroid administration. Even when steroid inhalation therapy was ineffective, systemic administration of PSL 5 mg/day effectively resolved chest imaging findings and respiratory symptoms. The successful steroid withdrawal rate was 18.5% overall, increasing to 23.8 and 42.9% in the PSL ≤ 10 mg/day and 5 mg/day groups, respectively.ConclusionApproximately one-third of patients received an initial steroid dose of PSL ≤ 10 mg/day for pulmonary sarcoidosis. This was mostly effective and the withdrawal rate was relatively high. Our results support that some Japanese patients with pulmonary sarcoidosis may successfully receive an initial dose of PSL ≤ 10 mg/day.